2007
DOI: 10.1007/bf03165781
|View full text |Cite
|
Sign up to set email alerts
|

Protecting antioxidative effects of vitamins E and C in experimental physical stress

Abstract: Like every redox-active compound vitamin E may exert pro-oxidative and antioxidative effects depending on the reaction partners present. In this work we evaluated the intensity of oxidative stress produced by a physical exercise through swimming as well as of protecting action of antioxidant vitamins E and C. Antioxidant systems include antioxidant enzymes: superoxide-dismutase (SOD), catalase (CAT), glutathion peroxidase (GSH-Px), as well as of components with an antioxidant action of the reduced glutathion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
15
0
2
Order By: Relevance
“…Protein carbonyl and TBARS, oxidative products of protein and lipid, respectively, are well known as useful markers for assessing oxidative stress in vivo (Hong and Johnson 1995;Sen et al 1997;Bejma and Ji 1999). Studies have shown that physical exercise can result in an increase in oxidative stress in vivo (Ji 1999;Alessio et al 2000;Ciocoiu et al 2007), which is known to play an important role in the muscle fatigue or damage in single muscle Wbers (Andrade et al 1998). Oxidative damage of proteins is accompanied by an increased number of carbonyl residues after endurance exercise in rat skeletal muscles (Levine et al 1990;Ji 1999).…”
Section: Catalase (Unit/mg Protein)mentioning
confidence: 98%
See 3 more Smart Citations
“…Protein carbonyl and TBARS, oxidative products of protein and lipid, respectively, are well known as useful markers for assessing oxidative stress in vivo (Hong and Johnson 1995;Sen et al 1997;Bejma and Ji 1999). Studies have shown that physical exercise can result in an increase in oxidative stress in vivo (Ji 1999;Alessio et al 2000;Ciocoiu et al 2007), which is known to play an important role in the muscle fatigue or damage in single muscle Wbers (Andrade et al 1998). Oxidative damage of proteins is accompanied by an increased number of carbonyl residues after endurance exercise in rat skeletal muscles (Levine et al 1990;Ji 1999).…”
Section: Catalase (Unit/mg Protein)mentioning
confidence: 98%
“…Control TRF-25 TRF-50 T-25 enzymes in the heart (Reznick et al 1982;Ciocoiu et al 2007), blood, liver and muscle (Lew et al 1985;Ji 1993), lung (Salminen et al 1984), and brain (Somani et al 1995). Therefore, antioxidant (e.g.…”
Section: Catalase (Unit/mg Protein)mentioning
confidence: 98%
See 2 more Smart Citations
“…The explanation may reside in the presence of antioxidant enzymes, as well as free radical scavengers, among which glutathione Stransferase (GSH) plays a key role. GSH performs several important physiological functions such as (a) inactivation of oxygen-derived highly reactive species [13,14]; (b) detoxification of various types of xenobiotics [13] and carcinogens [15]; (c) maintenance of the oxidative status of other antioxidants such as ascorbic acid and α-tocopherol [16]; and (d) improvement of cellular immune response by activation of lymphocytes [17].…”
Section: Introductionmentioning
confidence: 99%